PROGRESSIVE-ONTOGONISTIC PROPERTIES OF ARTIFICIAL AND NATURAL INTELLIGENCE - Jafar Mustafayev; Nasiba Inomjonova (Sciental Journals Publishing, 2025)
This article discusses the emergence, history, stages of development of artificial intelligence and natural human thinking, the contrasting characteristics of natural and artificial intelligence. It also describes the essence, role, and significance of artificial intelligence in current philosophical teachings, and the spiritual and moral relationship of man with artificial intelligence.
Keywords: Artificial intelligence, human worldview, natural intelligence, computer revolution, information, security, cybernetics, neural systems, technology, robots, evolutionary development.